ANALISIS USAHATANI KACANG TANAH DAN JAGUNG DI DESA KANONANG DUA KECAMATAN KAWANGKOAN BARAT - Nanchi Ester Sondakh; Ellen Grace Tangkere; Olly Esry Harryani Laoh (Sam Ratulangi University, 2019)
The purpose of this study was to compare whether peanut farming income was greater than corn farming in Kanonang Dua Village, Kawangkoan Barat District. This research was conducted for 3months starting from February to April 2019. Determination of farmer samples using a simple random sampling method. Data collected in this study are primary data and secondary data. Primary data wasobtained from direct interviews with 15 peanut farmers and 15 corn farmers so that the total respondents were 30 farmers. Secondary data was obtained from the Head of Village office of Kanonang Dua Village,Kawangkoan Barat Sub-district and Statistice office of Minahasa Regency and through the internet, through google searching to obtain scientific journals articles and Bachelor thesis from others university that related to the topic of this research. The results showed that the income received from peanut farming was greater than the income received by corn farming. Peanut farmer Rp.9,309,569 / Ha with a ratio of 2.33 while corn farmers Rp.3,427,500 / Ha with a ratio of 1.77.-*eprm*